Ultra High-Resolution FDTD Modeling of a High-Performance VLSI Package for Identifying Resonances and Coupling - Ruiz, César Méndez; Simpson, Jamesina J. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
It is becoming increasingly important to computationally predict, study, and prevent electromagnetic compatibility (EMC) issues arising within and between ICs and other components comprising portable electronic devices. Here, we conduct a phenomenological study involving an ultra high-resolution, threedimensional finite-difference time-domain (FDTD) model of a sample IC package having over one billion grid cells. Specifically, we determine the resonances and coupling patterns arising within the highly complex IC package. The frequency range of interest extends from 100 MHz to 7 GHz. Results indicate that the arrangement and geometry of the separate power, ground, and signaling networks comprising the IC package greatly influences the electromagnetic behavior within different regions of the package.